2019
DOI: 10.1111/1471-0528.15903
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness and safety of introducing condom‐catheter uterine balloon tamponade for postpartum haemorrhage at secondary level hospitals in Uganda, Egypt and Senegal: a stepped wedge, cluster‐randomised trial

Abstract: ObjectiveTo assess the effectiveness of introducing condom‐catheter uterine balloon tamponade (UBT) for postpartum haemorrhage (PPH) management in low‐ and middle‐income settings.DesignStepped wedge, cluster‐randomised trial.SettingEighteen secondary‐level hospitals in Uganda, Egypt and Senegal.PopulationWomen with vaginal delivery from October 2016 to March 2018.MethodsUse of condom‐catheter UBT for PPH management was introduced using a half‐day training and provision of pre‐packaged UBT kits. Hospitals were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(65 citation statements)
references
References 22 publications
0
59
0
5
Order By: Relevance
“…If uterine atony was not the main cause of refractory PPH, then the currently recommended treatment interventions would have limited impact to treat this complication, as they mainly target PPH caused by uterine atony. The results of a stepped‐wedge cluster randomised trial of a condom catheter UBT as an option for treatment of unresponsive postpartum bleeding in Egypt, Senegal and Uganda showed that this intervention was ineffective to reduce PPH‐related morbidity and mortality, and raised safety concerns . One of the possible reasons for this negative finding may be that the primary cause of poor outcomes in the study patients was not atony (which is what the UBT was intended to treat) but other causes.…”
Section: Introductionmentioning
confidence: 99%
“…If uterine atony was not the main cause of refractory PPH, then the currently recommended treatment interventions would have limited impact to treat this complication, as they mainly target PPH caused by uterine atony. The results of a stepped‐wedge cluster randomised trial of a condom catheter UBT as an option for treatment of unresponsive postpartum bleeding in Egypt, Senegal and Uganda showed that this intervention was ineffective to reduce PPH‐related morbidity and mortality, and raised safety concerns . One of the possible reasons for this negative finding may be that the primary cause of poor outcomes in the study patients was not atony (which is what the UBT was intended to treat) but other causes.…”
Section: Introductionmentioning
confidence: 99%
“…As reported for other balloon or suction tamponade devices, 2,4,5,[11][12][13] STUT may be carried out postpartum in the labour ward or in the operating theatre, with or without general or regional anaesthesia, after 20 weeks' gestation. Sterile precautions are maintained.…”
Section: Description Of the Methodsmentioning
confidence: 99%
“…Two randomised trials have reported poorer outcomes using a fixed volume improvised condom UBT in lowresource settings than without UBT. 4,5 Possible explanations include the balloon preventing the uterus contracting down, the type of balloons used, and implementation factors.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they delay the surgical management of the severe PPH, leading to a high rate of maternal mortality. 2 The major problem of condoms is that they cannot not be inflated more than 250À300 mL, as they explode afterward. In addition; their texture does not allow the efficient compression of the uterine cavity.…”
Section: To the Editorsmentioning
confidence: 99%